IMMUNOLOGICAL PROFILE OF WOMEN WITH ADENOMIOSIS AND HEALTHY WOMEN IN EXTRACORPORAL FERTILIZATION PROGRAMS - Виктория Васильевна Лихачева; Ольга Валентиновна Азарова; Татьяна Васильевна Третьякова; Людмила Владимировна Ренге; Светлана Владимировна Шрамко; Сергей Николаевич Филимонов; Борис Исаевич Айзикович (The Publishing House Medicine and Enlightenment, 2021)
Adenomyosis is a benign neoplastic process of the uterus, one of the forms of endometrioid disease. The negative impact of this pathology on the outcome of ART programs is associated with impaired implantation and loss of pregnancy in the early stages.We studied the levels of regulatory transport proteins (α2-MG, α1-AT, LF and ALB) and cytokines (IL-8, IL-6, TNF-α, INF-γ) in the blood serum of infertile patients with grade 1-2 adenomyosis and their influence on the outcomes of IVF programs. The study included 97 women. The main group consisted of 60 infertile patients with grade 1-2 adenomyosis, the comparison group consisted of 37 healthy women with male factor infertility.The embryos were cultured in one-step Irvine medium. The quality of embryos was assessed according to international standards (scale Gardner D.K. et al., 2001). Selective transfer of no more than 2 good quality embryos was performed on the 5th day of development. The effectiveness of IVF programs was assessed by the incidence of clinical pregnancy (CNB) according to ultrasound data on days 21-23 after embryo transfer. The study showed that the immunological profile of some factors of innate immunity: pro-inflammatory cytokines (TNF-α, IL-6, chemokine IL-8 and IFN-γ) and immunoregulatory proteins (a2-MG and a1-AT and Lf) in the blood serum of women with adenomyosis, entering the IVF program, has significant differences from the indicators of healthy women. In particular, they have decreased levels of a2-MG and a1-AT and increased concentrations of the cytokines TNF-α, IL-6, chemokine IL-8, and lactoferrin. Changes in indicators in response to CVD also differed in patients with adenomyosis and healthy women.Adenomyosis is a benign neoplastic process of the uterus, one of the forms of endometrioid disease. The negative impact of this pathology on the outcome of ART programs is associated with impaired implantation and loss of pregnancy in the early stages. We studied the levels of regulatory transport proteins (α2-MG, α1-AT, LF and ALB) and cytokines (IL-8, IL-6, TNF-α, INF-γ) in the blood serum of infertile patients with grade 1-2 adenomyosis and their influence on the outcomes of IVF programs.The study included 97 women. The main group consisted of 60 infertile patients with grade 1-2 adenomyosis, the comparison group consisted of 37 healthy women with male factor infertility.The embryos were cultured in one-step Irvine medium. The quality of embryos was assessed according to international standards (scale Gardner D.K. et al., 2001). Selective transfer of no more than 2 good quality embryos was performed on the 5th day of development. The effectiveness of IVF programs was assessed by the incidence of clinical pregnancy (CNB) according to ultrasound data on days 21-23 after embryo transfer.The study showed that the immunological profile of some factors of innate immunity: pro-inflammatory cytokines (TNF-α, IL-6, chemokine IL-8 and IFN-γ) and immunoregulatory proteins (a2-MG and a1-AT and Lf) in the blood serum of women with adenomyosis, entering the IVF program, has significant differences from the indicators of healthy women. In particular, they have decreased levels of a2-MG and a1-AT and increased concentrations of the cytokines TNF-α, IL-6, chemokine IL-8, and lactoferrin. Changes in indicators in response to CVD also differed in patients with adenomyosis and healthy women.